2015
DOI: 10.1371/journal.pone.0130483
|View full text |Cite
|
Sign up to set email alerts
|

Altered Resting-State Connectivity within Executive Networks after Aneurysmal Subarachnoid Hemorrhage

Abstract: Aneurysmal subarachnoid hemorrhage (aSAH) is associated with significant mortality rates, and most survivors experience significant cognitive deficits across multiple domains, including executive function. It is critical to determine the neural basis for executive deficits in aSAH, in order to better understand and improve patient outcomes. This study is the first examination of resting-state functional Magnetic Resonance Imaging in a group of aSAH patients, used to characterize changes in functional connectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…Another important question that animal studies may be able to address is why patients without frank brain injury following their hospitalization go on to have longstanding cognitive deficits. Human imaging studies suggest an association between measures of functional brain network connectivity and worse cognitive outcomes in survivors of aneurysm rupture [71,72]. However, it is not clear if the cognitive deficits are determined by altered functional connectivity or if functional connectivity is an epiphenomenon.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…Another important question that animal studies may be able to address is why patients without frank brain injury following their hospitalization go on to have longstanding cognitive deficits. Human imaging studies suggest an association between measures of functional brain network connectivity and worse cognitive outcomes in survivors of aneurysm rupture [71,72]. However, it is not clear if the cognitive deficits are determined by altered functional connectivity or if functional connectivity is an epiphenomenon.…”
Section: Mechanistic Studiesmentioning
confidence: 99%
“…4 Recent studies using functional neuroimaging have found an association between these persistent cognitive deficits and alterations in neuronal networks after SAH using fMRI or magnetoencephalography. 57 In one study, altered measures of resting state functional connectivity (RSFC) were associated with worse performance on the Montreal Cognitive Assessment, a test of mild cognitive impairment. 7 Another study found that altered RSFC was associated with decreased executive dysfunction and worse quality of life as measured by a battery of standard cognitive tests.…”
Section: Introductionmentioning
confidence: 99%
“…7 Another study found that altered RSFC was associated with decreased executive dysfunction and worse quality of life as measured by a battery of standard cognitive tests. 6 However, a causal relationship between altered functional connectivity and cognitive deficits is not yet established, in part because of a lack of experimental models.…”
Section: Introductionmentioning
confidence: 99%
“…Many survivors of SAH suffer from persistent cognitive problems [3] with the majority not being able to return to work or resume their previous activities [4]. Recent studies using functional neuroimaging have found an association between these persistent cognitive deficits and alterations in neuronal networks after SAH using fMRI or magnetoencephalography [5][6][7]. In one study, altered measures of resting state functional connectivity (RSFC) were associated with worse performance on the Montreal Cognitive Assessment, a test of mild cognitive impairment [7].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, altered measures of resting state functional connectivity (RSFC) were associated with worse performance on the Montreal Cognitive Assessment, a test of mild cognitive impairment [7]. Another study found that altered RSFC was associated with decreased executive dysfunction and worse quality of life as measured by a battery of standard cognitive tests [6]. However, a causal relationship between altered functional connectivity and cognitive deficits is not yet established, in part because of a lack of experimental models.…”
Section: Introductionmentioning
confidence: 99%